2009
DOI: 10.1007/s00244-009-9359-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal and Pesticide Levels in Soil and Plant Products from Agricultural Area of Belgrade, Serbia

Abstract: This study was aimed to assess the levels of selected heavy metals and pesticides in soil and plant products from an agricultural area of Belgrade, Serbia and to indicate possible sources and risks of contamination. Soil, vegetable, and fruit samples from the most important agricultural city areas were collected from July to November of 2006. Metal contents were determined by atomic absorption spectrometry, whereas pesticide residues were analyzed by gas chromatography-mass spectrometry after extraction perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 12 publications
1
38
0
3
Order By: Relevance
“…Results of research using external inputs of site-specific chemical fertilizers still contained heavy metals in the soil (0.54-1.32 ppm) [3]. Similarly, results of research in Belgrade Serbia reported that heavy metal contaminants from the Power Plant industry had detected Pb (13.4-27.4 mg / kg), Cd (0.11-0.27 mg / kg), Cu (20, 5-34.4 mg / kg), Zn (75.3-142 mg / kg) of land on agricultural land is still below established national and international standards [4]. Based on the above consideration, it is necessary to conduct an assessment aimed at identifying heavy metal content in terraced rice field in Sruwen Village, Tengaran District, Semarang Regency.…”
Section: Introductionmentioning
confidence: 95%
“…Results of research using external inputs of site-specific chemical fertilizers still contained heavy metals in the soil (0.54-1.32 ppm) [3]. Similarly, results of research in Belgrade Serbia reported that heavy metal contaminants from the Power Plant industry had detected Pb (13.4-27.4 mg / kg), Cd (0.11-0.27 mg / kg), Cu (20, 5-34.4 mg / kg), Zn (75.3-142 mg / kg) of land on agricultural land is still below established national and international standards [4]. Based on the above consideration, it is necessary to conduct an assessment aimed at identifying heavy metal content in terraced rice field in Sruwen Village, Tengaran District, Semarang Regency.…”
Section: Introductionmentioning
confidence: 95%
“…The research results indicate that the most often used SPME fibers in the pesticide residues analysis (PDMS and PA) are a good choice for determination of: phenyl urea in carrot, onion and potato (Berrada et al, 2004); OCPs in soils (Zhao et al, 2006;Herbert et al, 2006); OPPs in strawberries and cherries (Lambropoulou i Albanis, 2003) and samples of banana, apple, grapefruit, orange, lemon, kiwi, pineapple, pear, peach, apricot, grapes, melon, lotus, plum, mango, cherry and coconut (Fytianos et al, 2006); OCPs and OPPs in cucumber and strawberry (Kin & Huat, 2010); pesticides belonging to different chemical groups in tomato and cucumber (Chai & Tan, 2009), mango (Filho et al, 2010), soil (Đurović et al, 2010a, 2010b), i.e. in samples of potato, tomato, onion, cabbage and pepper (Marković et al, 2010). Considering that in the SPME analysis only 1 cm of fiber is exposed to the sample, not only the nature, but also the size of the active surface layer will significantly affect the microextraction efficiency.…”
Section: Fig 2 Procedures For Microextraction Of Analytes From Solutionmentioning
confidence: 99%
“…polarni polarnim. Istraživanja sprovedena u oblasti ostataka pesticida ukazuju da su u najvećem broju sluča-jeva vlakna sa izrazito nepolarnim polidimetil-siloksanskim (PDMS) i izuzetno polarnim poliakrilatnim (PA) aktivnim slojevima najefikasnija u analizama uzoraka različitog porekla (Doong i Liao, 2001;Sakamoto i Tsutsumi, 2004;Đurović, 2006;Đurović i sar., 2007;2007a;2010;2010c;Fernandez-Alvarez i sar., 2008), tako da će u ovom radu biti prikazane osnovne karakteristike samo ova dva mikroekstrakciona sorbenta.…”
Section: Izbor Spme Vlaknaunclassified
“…Količina sorbovana na vlaknu i vreme uravnotežavanja zavisiće od debljine i polarnosti aktivnog sloja vlakna, distribucionih konstanti analita i eksperimentalnih uslova (način i brzina mešanja uzorka, temperatura, itd.). Iako se maksimalna osetljivost SPME metode postiže na ravnotežnim vremenima, iz praktičnih razloga ekstrakciono vreme se može skratiti (Pawliszyn, 1997;Đurović, 2006, 2010Đurović i sar., 2007, 2010b, 2010c.…”
Section: Optimizacija Uslova Ekstrakcijeunclassified